Design and evaluation of valsartan fast dissolving tablets as a new super disintegrant of ocimum gratissimum mucilage - A.BHARATHI,; D.CHANDRA SEKHAR NAIK, (International Journal of Pharma and Bio Sciences, 2019)
The main objective of present investigation is to evaluate Ocimum gratissimum mucilage as a super disintegrate in the formulation of fast dissolving tablets of poorly soluble drugs employing 23 factorial design. The mucilage was obtained by isolation process and it was subjected to physical and micromeritic evaluation. To establish as mucilage as a super disintegrate, fast dissolving tablet of valsartan was prepared employing Ocimum gratissimum mucilage in different proportions in each case by direct compression method employing 23 factorial design. All fast dissolving tablets prepared were evaluated for drug content, hardness, friability, disintegration time and other dissolution characteristics like percent dissolved in 5 min (PD5), Dissolution efficiency in 5 Min (DE5%) and first order rate constant(K1). The mucilage was found to be fine, free flowing slightly crystalline powder and it exhibited good swelling in water. Fourier transform infrared spectra (FTIR) and Differential scanning calorimetry (DSC) study indicated the absence of interaction between valsartan and mucilage. All the fast dissolving tablets formulated employing mucilage were of good quality with regard to drug content (100±5%), hardness (3.6–4 kg/sq. cm), and friability (0.05-0.19%). Disintegration time for FDTs was determined using USP disintegration apparatus 0.1 N HCl buffer. The volume of medium was 900 ml and the temperature was 37±0.2 °C. The time in second taken for complete disintegration of the tablet with no palatable mass remaining in the apparatus was measured. Mucilage was found to be a superdisintegrant which enhanced the dissolution efficiency when combined with sodium starch glycolate, croscarmellose sodium, with the valsartan and hence it could be used in the formulation of fast dissolving tablets to provide immediate release of the contained drug within 5 min.